PENGARUH TECHNOLOGY INTEGRATION, DIGITAL LITERACY DAN PERCEIVED EASE OF USE TERHADAP CONSUMER NEEDS FOR UNIQUENESS - Kurniawan, Dian; Rosyadi, Agi (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2020)
ABSTRACTOne form of fulfilling the need to be different (Consumers Need for Uniqueness) in the millennial generation can be realized by making online purchases (online shopping). Purchasing in this way allows a more complete search process as more information becomes available. This of course must be a concern of marketers. Selling through the online shop system must be a new strategy to win the competition. The first challenge that must be faced is how companies can integrate technology (technology integration), which is owned in order to create a marketspace that makes someone feel confident that the information system is easy to use and provides a different sensation of experience. Perceived ease of use, apart from providing a good interface, will also depend on the level of technology literacy. The various levels of technological literacy in society are certainly a challenge in itself. The objective of this research was to determine the effect of Technology Integration, Digital Literacy, Perceived Ease Of Use on Consumer Needs For Uniqueness. The research method is a survey with a research instrument in the form of a questionnaire that has been distributed to respondents who make purchases by choosing an online store. The data were processed using the SEM method. The results show that only Digital Literacy has an effect on Consumer Needs for Uniqueness while Technology Integration and Perceived Ease Of Use have no effect. Digital literacy has an impact because the ability to use digital technology can optimize the fulfillment of unique needs.Keywords: technology integration; technology literacy; perceived ease of use; consumer needs for uniqueness; millennial generationABSTRAK Salah satu bentuk pemenuhan kebutuhan untuk tampil beda (Consumers Need for Uniqueness) pada generasi milenial dapat diwujudkan dengan cara melakukan pembelian secara online (onlineshopping). Pembelian dengan cara seperti ini memungkinkan proses pencarian yang lebih lengkap karena informasi yang tersedia menjadi lebih banyak. Hal ini tentunya harus menjadi perhatian para pemasar. Penjualan melalui sistem onlineshop harus menjadi strategi baru untuk memenangkan persaingan. Tantangan pertama yang harus dihadapi adalah bagaimana agar perusahaan dapat mengintegrasikan teknologi (technology integration), yang dimiliki agar tercipta sebuah marketspace yang membuat seseorang merasa percaya bahwa sistem informasi tersebut mudah digunakan dan memberikan sensasi pengalaman yang berbeda. Persepsi kemudahan penggunaan (perceived ease of use) selain dapat diwujudkan dengan menyediakan interface yang baik juga akan tergantung pada tingkat literasi teknologi (technology literacy). Tingkat literasi teknologi yang beragam di masyarakat tentunya menjadi tantangan tersendiri. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh Technology Integration, Digital Literacy, Perceived Ease Of Use terhadap Consumer Needs For Uniqueness. Metode penelitian adalah survey dengan instrumen penelitian berupa kuesioner telah disebarkan kepada responden yang melakukan pembelian dengan memilih toko online. Data diolah dengan menggunakan metode SEM. Hasil penelitian menunjukkan bahwa hanya Digital Literacy yang berpengaruh terhadap Consumer Needs For Uniqueness sementara Technology Integration dan Perceived Ease Of Use tidak memiliki pengaruh. Literasi digital memiliki pengaruh karena kecakapan penggunaan teknologi digital dapat mengoptimalkan pemenuhan kebutuhan keunikan.Kata Kunci: technology integration; technology literacy; perceived ease of use; consumer needs for uniqueness; millennial generation